Manajemen Perawatan Kompresor Udara Pada Mesin Induk di KM Umsini - Haryadi, Sugeng; Pratomo, Sunu Arsy (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The smooth operation of the ship is inseparable from the support of auxiliary aircraft with good work and maintenance systems. The compressor as a producer of compressed air which will be used for the initial ignition of the main engine, and auxiliary engines as well as working air services in the engine section and the deck section. Thus, maintenance needs to be carried out so that the required air capacity can be fulfilled at any time. For the smooth operation of the machine, good maintenance management is needed so that its condition is maintained and when it is used there are no problems and it can work optimally. Many experts say that how important it is to make a good maintenance management. The method used in this research is the field research method supported by conducting interviews with several parties related to the research topic and supported by library research methods. To carry out maintenance and repairs to the air compressor on the main engine at KM Umsini, it is necessary to carry out maintenance and repair management which includes planning, organizing, implementing and finally controlling. The suggestion that the author can convey is that the ship's crew, especially the engineers, learn correctly the workings or functions of the air compressor on the main engine so that when the ship is operating it experiences problems that can be resolved properly.